Comprehensive Physiology 2020
DOI: 10.1002/cphy.c190025
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon‐Like Peptide‐1: Actions and Influence on Pancreatic Hormone Function

Abstract: GLP-1 was described as an incretin over 30 years ago. GLP-1 is encoded by the preproglucagon gene (Gcg), which is expressed in the intestine, the pancreas, and the central nervous system. GLP-1 activates GLP-1 receptors (GLP-1r) on the β-cell to induce insulin secretion in a glucosedependent manner. GLP-1 also inhibits α-cell secretion of glucagon. As few, if any, GLP-1r are expressed on α-cells, indirect regulation, via β-or δ-cell products has been thought to be the primary mechanism by which GLP-1 inhibits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 260 publications
0
21
1
2
Order By: Relevance
“…DART-Seq improves detection of low-abundance transcripts in human islets. A growing body of literature reports that turning on α cell GLP-1 production potently improves islet function and glucose homeostasis (10,16,17,24,30,31). PC1/3 expression is required for α cell GLP-1 production; however, the mechanisms regulating α cell PC1/3 expression are poorly defined.…”
Section: Resultsmentioning
confidence: 99%
“…DART-Seq improves detection of low-abundance transcripts in human islets. A growing body of literature reports that turning on α cell GLP-1 production potently improves islet function and glucose homeostasis (10,16,17,24,30,31). PC1/3 expression is required for α cell GLP-1 production; however, the mechanisms regulating α cell PC1/3 expression are poorly defined.…”
Section: Resultsmentioning
confidence: 99%
“…Intestinal GLP-1 secretion is induced by duodenal gastric inhibitory polypeptide (GIP) and muscarinic vagal stimulation [191]. Its physiological roles comprise: controlling fasting plasma glucagon, potentiating pancreatic insulin release, influencing motoric mechanisms of gastric emptying, and inhibiting short-term food intake [262,278] (for review, [62]). Both, sweet-taste receptor-dependent and sweettaste receptor-independent mechanisms were proposed for GLP-1 release by L cells, depending on species, intestinal region, and site of application [35,268].…”
Section: Role Of Glucagon-like Peptide-1 In the Alternative Pathwaymentioning
confidence: 99%
“…GLP-1RA may influence the activity of two opposite subgroup neurons within ARC, which are related to food intake and body weight, containing proopiomelanocortin/cocaine- and amphetamine-regulated transcript (POMC/CART) and neuropeptide Y/agouti related peptide (NPY/AgRP) neurons; 137 , 157 In PVN, 158 , 159 GLP-1RA particularly, has been shown to interact with neuropeptides, such as AVP, oxytocin, and CRH release, thereby regulating eating and stress; BNST, 160 , 161 which is associated with suppression of food intake and stress response; LPB, 162 which reportedly mediates food intake and reward; hippocampus, 163 which influences cognition performance for food intake in rodents; NTS, 164 a major critical knot for afferent signals of gastro-intestine and satiety; VTA 165 , 166 and NAc, 167–169 which process reward for food and drug behavior; amygdala 170 , 171 that influences glucose homeostasis and food reward; as well as HPA-axis 172 , 173 which could affect stress and SNS. 174 Previous studies have reported the comprehensive effects of GLP-1RA on the CNS, which go beyond the levels of blood glucose modulation, but are associated with numerous metabolic aspects such as food intake and preference, 127 , 175 water intake, 176 energy expenditure, 177 body weight reduction, 178 pancreatic function, 132 , 179 , 180 hypertension, 181 stress, 182 addiction behaviors, 183 , 184 as well as neurodegenerative disorders, such as Alzheimer and Parkinson diseases. 185 These metabolic effects have proved versatile central actions of GLP-1RAs, and have been associated with direct or indirect potential secondary benefits like reduced risks of dyslipidemia, anti-atherosclerosis, modulation of cardiovascular activity, and proteinuria, as well as influencing clinical outcomes in T2D patients.…”
Section: Central Nervous Pathways Associated With Glp-1ras’ Treatment Outcomesmentioning
confidence: 99%